2021
DOI: 10.3390/microorganisms9122601
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Modulation of the Immune Response Mediated by Nucleotides in Canine Leishmaniosis

Abstract: Leishmaniasis is an emerging, uncontrolled, and neglected zoonotic disease. Climate change is contributing to its ongoing global expansion. The dog is the main reservoir; hence the importance of implementing effective treatment, prevention, and control measures in this animal species to protect public health. However, although the standard treatment for canine leishmaniosis (CanL) is effective, it does not provide full parasitological clearance, and side effects and drug resistance have been described. The hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 195 publications
(288 reference statements)
0
11
0
Order By: Relevance
“…Nucleotides are low-molecular-weight intracellular compounds which, besides being the building blocks of DNA and RNA, play important roles in physiological and biochemical processes [ 20 , 34 , 35 ]. They have also been reported to improve shrimp health by modulating their immune response [ 21 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleotides are low-molecular-weight intracellular compounds which, besides being the building blocks of DNA and RNA, play important roles in physiological and biochemical processes [ 20 , 34 , 35 ]. They have also been reported to improve shrimp health by modulating their immune response [ 21 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, several publications support the benefits of Nucleoforce ® , a proprietary brand of nucleotide-rich yeast extract developed by Bioiberica S.A.U. (Palafolls, Spain), which is highly sustainable, as it can be obtained through a fermentation process following a circular bioeconomy approach [ 20 ]. In a recent study with this nucleotide extract in PWS, our research group demonstrated a positive effect in PWS receiving diets in which fish meal (FM) had been partially replaced with soybean meal (SBM).…”
Section: Introductionmentioning
confidence: 99%
“…Dogs with stage 1 CanL have mild disease that can go undetected by the owner, which is the most likely reason why they were underrepresented with only three included in this study. High parasitic load is associated with more intense immune complex formation, greater serum IFAT titers, and more severe clinicopathological manifestations of the disease [ 2 , 3 , 40 ] Due to the exclusion criteria of the present study, we only included one dog with stage 4 CanL. Consequently, the lower parasite population in lung tissue and, therefore, milder lesions could be justified by the milder cases enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of the infection ranges from local elimination of the parasite to parasite dissemination and development of mild to severe clinical signs and/or clinicopathological abnormalities. Cells of the mononuclear phagocytic system, neutrophils, eosinophils, hepatocytes, endothelial and dendritic cells, and fibroblasts can be infected by Leishmania parasites; therefore, a variety of different organs can be affected, justifying the clinical polymorphism of the disease [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In weaned mice, supplementation with dietary NTs modulates a proportion of gamma-delta T cells in the gut intraepithelial lymphocyte compartment, enhances interleukin 7 and antigen-specific IgA responses produced by gut epithelial cells, inhibits antigen-specific IgE antibody responses, and promotes the development of the early gut mucosal immune system (Nagafuchi, 2007). NT supplementation can also promote increases of immune factors, such as IgA, IgM, and insulin-like growth factor 1, in the GIT in the early stage of life and reduce the levels of inflammatory factors such as cortisol and tumor necrosis factor-alpha (TNF-α) in the body (Segarra, 2021). The elevated concentration of adenosine in vivo can activate adenosine A2a receptors on the surfaces of immune cells and gut epithelial cells and is expected to be a potential target for the treatment of chronic enteritis (Ye & Rajendran, 2009).…”
Section: Dietary Nts and Gut Immune Development In Early Lifementioning
confidence: 99%